Cognitive, Emotive and Behavioural Aspects of Eating Habits in University Students of Lahore, Pakistan - Amir Sheikh, Iman; Zafar, Arsia; Fatima, Syeda Aeliya; Arshad, Hiba; Saleem, Maira; Majeed, Saima (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The prevalence of poor dietary habits and unhealthy food consumption has increased tremendously in recent years, particularly among university students. Aim: To look at the cognitive, emotive, and behavioural aspects of eating habits in undergraduate students of Lahore Pakistan. Methods: Cross Sectional study. The sample consisted of 278 undergraduate university students aged from 18 to 25 years (M =20.75, SD=1.61) from various institutes of Lahore using a non-probability convenient sampling technique. The Three Factor Eating Questionnaire (R18) along with a demographic sheet was used as the measure of assessment in this study.Data was evaluated by using SPSS version 26. Pearson’s correlation was applied. Results: The results showed that there are different reasons for the eating habits of university students like uncontrollable eating, cognitive restraint, and emotional eating. There was a significant difference in scores for men (M=21.95, SD=4.60) and women (M=23.46, SD= 4.24: t (276) = -2.74, p= .007) in the uncontrolled eating domain. However, no significant gender differences were found in the cognitive restraint and emotional eating domains. Moreover, the findings also revealed that the students' eating habits were unaffected by their fast-food consumption or by them being day scholars or hostelites/boarders. Practical Implication: This research study will contribute to the development of innovative research on eating habits in Pakistani culture and society. This study will also assist to fill a gap in the existing literature by combining these two factors, and it may also inspire other new studies with various concepts and diverse demographic samples. Conclusion: It was concluded that unhealthy eating practices by students are on the rise all around the world, including Pakistan.